PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. X BEKASI - Fansuri, Lutfi (University of Riau Kepulauan, 2021)
This research has purpose to explain the influence simultaneously and partially of occupational safety and health to employee performance in CV. X. The research conducted is the research the type associative. The number of samples in this study 12 people employees CV. X. Data collection techniques used in this research is questionnaire and interviews. he results showed that the variables of work safety and health work simultaneously significant effect on employee performance with significance 0.001 < 0.05 and the value of Adjusted R square of 0,741. This shows that the contribution of the variable of occupational safety and health on employee performance is equal to 74,1%. Partial variable safety have a significant effect on employee performance of is 0.009. While the variable of occupational health no significant effect on employee performance of 0,604.